(untitled) (Journal of Economic Additions, 2020)
We aim from this study to know the extent of the economic Enterprise commitment to applying social responsibility accounting, by addressing the concepts of social and environmental responsibility and their accountability, then trying to know the extent of the Enterprise adoption of social and environmental responsibility through two aspects, namely the areas of social and environmental responsibility, and the Enterprise disclosure of its responsibility Environmental and social, using the questionnaire. The study concluded that social and environmental responsibility is of great importance to the Enterprise itself, the environment and society. As for the Enterprise under study, we find a kind of awareness of the areas of social and environmental responsibility, and it discloses its social and environmental responsibilities within its annual financial reports through information related to its social and environmental performance. Keywords: Accounting for social and environmental responsibility; areas of social responsibility; accounting disclosure. Jel Classification Codes: M41؛ M14؛ Q20.